A review of research on teaching of computer programming in primary school mathematics: moving towards sustainable classroom action - O.E. Holo; E.N. Kveim; M.S. Lysne; L.H. Taraldsen; F.O. Haara (Education Inquiry, 2023)
ABSTRACTThis review article focuses on the teaching of computer programming in primary school mathematics, as reported by 37 empirical studies. Our findings show that a variety of research methods are used, which often combine qualitative and quantitative approaches. Furthermore, we found the focus of attention to vary from emphasis on the teacher and the teacher’s knowledge regarding computer programming, to how use of tools and devices can influence learning outcomes, and the actual teaching and learning in the classroom. We found the implications for teaching congregate in three categories: the relation between mathematics and computer programming, tools and devices, and didactical approaches. Based on the discussion of our findings, we suggest two new possibilities for research on the teaching of computer programming in primary school mathematics: focus on computer programming and specific mathematical topics, and focus on students’ in-depth learning in a way that makes it possible to explore connections between computer programming and mathematics and use of computational thinking to solve mathematical problems.